Trade Correspondence between Kumyk Feudal Lords with the Russian Military Administration in the Caucasus in the 1740’s–1760’s (Based on the Materials of the Central State Archive of the Republic of Dagestan) - M.-P. B. Abdusalamov (Вестник Кемеровского государственного университета, 2019)
The research was based on the documents of funds 339 "Campaign Office of Lieutenant General A. P. Devits" and 379 "Kizlyar commandant". The documents were obtained from the Central State Archive of the Republic of Dagestan. The paper focuses on the trade correspondence between Kumyk rulers with the Russian military authorities in the Caucasus in the 1740’s–1760’s. The documents of the Campaign Office of Lieutenant General A. P. Devits and the Kizlyar curfew archive illustrate that the trade and economic ties between the Kumyks and Russia grew quite intensive by the middle of the XVIII century. Most part of the material has never been studied before. Kumyk rulers were interested in trade with the city of Kizlyar, as well as other Russian cities. The subsistence economy of Kumykia could not fully provide for the growing domestic needs of the local population, e.g. industrial products. According to their letters to the Kizlyar commandants, the Kumyk rulers sought to create favorable conditions for the local merchants – savdagars – in order to protect them from highway robberies. The gradual integration of the Kumyk lands into the all-Russian market contributed to their economic growth and the development of the productive forces in the region. At the same time, the trade was mutually beneficial. The savdagars imported raw silk, madder, and cotton, which were important for the development of domestic Russian industry.